A comprehensive analysis of delamination and thermoelectric performance of thermoelectric pn-junctions with temperature-dependent material properties. (1st December 2019) - Cui, Y.J.; Wang, K.F.; Wang, B.L.; Li, J.E.; Zhou, J.Y.
Abstract: Thermoelectric (TE) materials are temperature-sensitive and have great application potential in the field of renewable energy. Considering the TE effects including Joule heating, Thomson effect, Fourier heat conduction, convection and radiation, this paper evaluates the power output, energy conversion efficiency and bending induced delamination of the TE pn-junction. The TE models with temperature-dependent and equivalent (constant) material properties are discussed respectively. The homotopy perturbation method and finite difference scheme are employed to solve the strong nonlinear thermal-electric-stress coupled field. Analytical solutions of temperature fields, power output and energy conversion efficiency are derived. The axial forces, interlaminar stresses and energy release rates are presented in numerical forms. It is found that the power output and energy conversion efficiency are underestimated under equivalent material properties. The figure of merit could not be used as a criterion to assess the TE performance of temperature-dependent TE devices. Taking the temperature dependence of material properties into account, the axial forces and interlaminar stresses in the TE pn-junction are much bigger than the equivalent model. The critical temperature of delamination propagation is greatly overestimated without considering the temperature dependence of material properties.